2020
DOI: 10.1042/bcj20190596
|View full text |Cite
|
Sign up to set email alerts
|

A lysosome independent role for TFEB in activating DNA repair and inhibiting apoptosis in breast cancer cells

Abstract: Transcription factor EB (TFEB) is a master regulator of lysosomal biogenesis and autophagy with critical roles in several cancers. Lysosomal autophagy promotes cancer survival through the degradation of toxic molecules and the maintenance of adequate nutrient supply. Doxorubicin (DOX) is the standard of care treatment for triple-negative breast cancer (TNBC); however, chemoresistance at lower doses and toxicity at higher doses limit its usefulness. By targeting pathways of survival, DOX can become an effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 83 publications
1
32
0
Order By: Relevance
“…Previous studies showed that proinflammatory cytokines and ceramides induce apoptosis (36). Our functional analyses of DEGs in EP highlighted the enrichment in the MF group of apoptosis-associated systems such as protein ubiquitination, ATM, ceramide, death receptor signaling, and NER pathways (37)(38)(39)(40)(41)(42). In further support of our results, a recent in vitro study showed that human milk reduced cellular apoptosis in intestinal epithelial cells through the inhibition of oxidative stress (43).…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies showed that proinflammatory cytokines and ceramides induce apoptosis (36). Our functional analyses of DEGs in EP highlighted the enrichment in the MF group of apoptosis-associated systems such as protein ubiquitination, ATM, ceramide, death receptor signaling, and NER pathways (37)(38)(39)(40)(41)(42). In further support of our results, a recent in vitro study showed that human milk reduced cellular apoptosis in intestinal epithelial cells through the inhibition of oxidative stress (43).…”
Section: Discussionsupporting
confidence: 87%
“…Several genotoxic stressors inducing DDR such as etoposide, cisplatin, UVC, and doxorubicin can induce TFEB nuclear translocation [26,45]. Indeed, we found that TFEB activation is essential to induce p21 up-regulation upon treatment with the DNA-damage agent doxorubicin.…”
Section: Discussionmentioning
confidence: 69%
“…NEAT1 is important for gene stability [44]. A previous study showed that Dox promoted cellular damage though impairing gene stability [45]. Moreover, silencing lncRNA-NEAT1 in MSCs, even MSCs treated with MIF, could not exert a cardioprotective effect, with shortened telomere length and impaired telomerase activity, both important in gene stability [46].…”
Section: Discussionmentioning
confidence: 99%